Telaah: self-care mobile application untuk pencegahan luka diabetes - Untari, Eka Kartika (Sasambo Journal of Pharmacy, 2025)
Self-care practices and appropriate glycemic management may prevent diabetic ulcer, a complication that has a detrimental effect on patients and their families. Through mobile-health applications, educational initiatives can increase patient awareness and promote the early preventative measures required to minimize complications from diabetes. The purpose of this review of the literature is to investigate research on the development of mobile-health applications for people with diabetes. The articles reviewed were obtained through keyword searches in the PubMed and Google Scholar databases within the last 10 years. According to seven published articles, six applications were created as self-care resources for people with diabetes mellitus. In order to prevent diabetic ulcer, mobile-health applications might assist people with diabetes maintain their independence in self-care routines.